Bank Indonesia Syariah Certificate: Encouraging Economic Growth During The COVID-19 Pandemic - Purnomo, Agus; Zahra Maulida, Atika; Fatimah Tuzahra, Siti; Lestari, Dian Ayu (AL-QARDH, 2023)
The Bank Indonesia Sharia Certificate (SBIS) is one of the sharia monetary instruments used by Bank Indonesia in formulating monetary policy. The development of SBIS is related to several factors: inflation growth, the economy, and the development of the gross domestic product. This study aims to determine how to implement the Bank Indonesia Sharia Certificate (SBIS) in encouraging monetary economic growth during the